Auditoria de gestión al gobierno autónomo descentralizado del cantón Pindal durante el periodo 01 de enero al 31 de diciembre del 2012 - Conde Montaño, Lilian Rocío (2016)
The present denominated thesis work "Audit of Administration to the Decentralized Autonomous Government of the Canton Pindal during the Period January 01 at December 31 the 2012", their objectives were guided: To evaluate the internal check system implemented by the Institution, to Verify the execution of the laws and regulations to those that the Institution is governed, to Carry out the FODA to identify the internal and external factors that favor him and they hinder its institutional administration and to Apply indicators to measure the grade of efficiency, effectiveness and quality that it toasts to the society. The methodology that was used to give execution before with the objectives exposed it was developed based on what prepares the Manual of Audit of Administration emitted by the General Controllership of the State, applicable for the Public Institutions. The acquired results as for the Component of Human resource, Financial and Material during the trial of the Audit of Administration to the Municipal Government you ended up determining that: most of the personnel lacks knowledge about the mission, vision and manual of functions, it exists the lack of application of indicators that allows to measure their administration, as for the personnel they don't receive trainings on the part of the institution and in a great percentage neither have an in agreement professional title to the position that you/they occupy, some of the workers they are untimely a hour of entering to their work, the economic resource is insufficient to finance all the municipal works and in the different departments the space is reduce for the development of the activities and in cellar for the storage of materials. Through the obtained results you ended up concluding that: The internal check system is inefficient because they have not been carried out administration audits that allow to measure the execution of the activities and the appropriate handling of its resources. Also the selection and training of the personnel is not carried out in a correct way preventing them to act better in the labor field, The budget designated by the Government is little to cover with all the necessities that it possesses the Institution. It is in and of itself that it is recommended that he/she is carried out an administration audit that he/she helps to promote the optimization of the administration as well as the design of indicators to measure the grade of efficiency and effectiveness the same ones that contribute to the achievement of objectives and goals. In the related to the selection and training is indispensable that a training plan is implemented that allows him to be endowed with necessary knowledge to occupy its workstations and the personnel's selection they carry out it through a competition of merits and opposition with the purpose of to obtain a bigger yield and to elevate the quality of its work, it is also suggested that the Municipality carries out a correct budgetary planning to use of a better way their budget and it can fulfill all the planned works. With the previously exposed thing it is necessary that he/she takes in consideration the summations and recommendations so that they can take measured correctives that contributes to change the current situation of the Institution.